EKSPRESI EMOSI KELUARGA YANG MERAWAT PASIEN SKIZOFRENIA - Jek Amidos Pardede (Jurnal Ilmiah Keperawatan IMELDA, 2020)
Expression of emotions in the family can be an expression that reflects the high expression of negative emotions. Expressions of high emotion show an attitude that is full of criticism and hatred. It arises when parents or other family members assume that the disorder is influenced by internal factors and must be controlled by the individual. This study aims to determine the emotional expression of the family of schizophrenic patients in the mental hospital. Prof. dr. Muhammad Ildrem Medan. The research design used was descriptive with a cross-sectional approach. The population in this study were all families who have family members with outpatient schizophrenia patients at Prof. dr. Muhammad Ildrem Mental Hospital in Medan as many as 900 people. The sample of this research is 90 families. The sampling technique uses purposive sampling. The data collection tool used a questionnaire of 18 statements that had been tested for validity and reliability. The results showed the majority of respondents who treated patients had low emotional expressions, and the majority of respondents who treated more than one patient had high emotional expressions. Therefore, this research is expected to give attention to the families of sick family members to assist them in healing their illnesses.